The Clinical Utility of the NAB Judgment Subtest Among Individuals Diagnosed With Schizophrenia Spectrum Disorder Within a Forensic Inpatient Setting. (December 2022) - Roye, Scott; Coffey, C. Adam; Nitch, Stephen R.; Glassmire, David M.; Kinney, Dominique I.
Executive functioning (EF) has been identified as a significant predictor in determining competence to stand trial. Individuals deemed incompetent to stand trial are provided a limited time frame before conservatorship is considered, thus, treatment providers practicing within inpatient facilities have a responsibility to efficiently identify factors that may lead to prolonged hospitalizations, in order to avoid delays in a defendant's legal proceedings. Although previous studies have demonstrated the utility of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) Total Index Score in predicting length of stay (LOS), the Neuropsychological Assessment Battery (NAB) Judgment subtest provides a measure of executive function, which is a domain not captured by the RBANS. The current study examined the relationship between both the RBANS and NAB Judgment performance as predictors of LOS among 63 individuals diagnosed with schizophrenia spectrum disorders undergoing competency restoration treatment. Additionally, sensitivity analyses were used to determine cutoff scores for individuals requiring additional competency services. Results indicated that the NAB Judgment subtest was more predictive of LOS than the RBANS Total Index Score. Additionally, a raw score of ≤9 on NAB Judgment was indicative of increased LOS. These results highlight the utility of the NAB Judgment subtest within a forensic inpatient setting.